CHILDHOOD AND A CULTURE OF FEAR IN LEMONY SNICKET’S A SERIES OF UNFORTUNATE EVENTS - Annapurna, Nur Aini; Hapsarani, Dhita (UI Scholars Hub, 2019)
This article is an excerpt from an undergraduate thesis of the same title which focuses on A Series of Unfortunate Events, a children‟s book series by Lemony Snicket. This thesis explores how a culture of fear shapes childhood, which is represented in the series. By using qualitative textual analysis the research discusses how the series represent the way childhood is shaped by a culture of fear through the depiction of various characters and social institutions in the novels. This research also explores the author‟s attempts in challenging the notion that children are vulnerable by analyzing the Baudelaires‟ identity and vulnerability. Results suggest that A Series of Unfortunate Events demonstrates ambivalence in the perception of childhood. Social institutions that should create a safe space for children tend to further perpetuate the culture of fear for them. Furthermore, children‟s vulnerability is often taken advantage of by adults for their own interests. Results also suggest that for children, their childhood is shaped by a culture of fear that is created and maintained by adults